(untitled) (Journal of Engineering, 2023)
Biometrics is widely used with security systems nowadays; each biometric modality can be useful and has distinctive properties that provide uniqueness and ambiguity for security systems especially in communication and network technologies. This paper is about using biometric features of fingerprint, which is called (minutiae) to cipher a text message and ensure safe arrival of data at receiver end. The classical cryptosystems (Caesar, Vigenère, etc.) became obsolete methods for encryption because of the high-performance machines which focusing on repetition of the key in their attacks to break the cipher. Several Researchers of cryptography give efforts to modify and develop Vigenère cipher by enhancing its weaknesses. The proposed method uses local feature of fingerprint represented by minutiae positions to overcome the problem of repeated key to perform encryption and decryption of a text message, where, the message will be ciphered by a modified Vigenère method. Unlike the old usual method, the key constructed from fingerprint minutiae depend on instantaneous date and time of ciphertext generation. The Vigenère table consist of 95 elements: case sensitive letters, numbers, symbols and punctuation. The simulation results (with MATLAB 2021b) show that the original message cannot be reconstructed without the presence of the key which is a function of the date and time of generation. Where 720 different keys can be generated per day which mean 1440 distinct ciphertexts can be obtained for the same message daily.